From Lifeless Numbers to the Vital Nerve of Democracy: Dolf Sternberger's Metaphorical Argumentation against Proportional Voting - Pankakoski Timo (Cambridge University Press, 2025)
This article analyzes Dolf Sternberger's post-World War II argumentation against proportional representation. Sternberger is central in the intellectual history of German democratization. However, he expressed his misgivings about parties and proportionality in a perplexingly antidemocratic register. Proportionality was anonymous, mechanical, dead, and purely mathematical, relying on “mere numbers” and “summing up” as opposed to living, dynamic, and organic political relations—ultimately not a form of political electing at all. Sternberger intentionally mobilized age-old topoi and metaphors which interwar antidemocratic authors had used against parliamentary democracy in its entirety, now skillfully redirecting their force against proportional representation more specifically. Sternberger's intricate metaphorical system linked his anti-proportional views to his theory of active civic engagement and ultimately served pro-democratic aspirations in the altered historical situation. His case exemplifies broader continuities between interwar and postwar discourses and highlights the need to read metaphorical argumentation in historical contexts and pragmatically rather than merely semantically.